Network Evaluation as a Complex Learning Process - Weber, Susanne (Journal of MultiDisciplinary Evaluation, 2005)
The following contribution will explicate, based on an understanding of networking as a reflexive process and on an approach working from a theory of regulation, one set of criteria for the development of evaluation designs in a networking context. Needs for evaluation and monitoring that is action- and future-oriented lead to other needs already established by social-ecological planning theory. From these can be generated questions for decisions in monitoring and evaluation within complex actor settings as well as criteria for concepts of evaluation and monitoring in a networking context. On this basis, four dimensions of network evaluation and monitoring are suggested and they are embedded in the multi-dimensional design approach of the “learning network” which puts collective competence development and future- and effect-orientation at the center of the developmental process.